1995
DOI: 10.1088/0268-1242/10/1/011
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electronic properties of Bi-modified amorphous thin films of Ge20Te80-xBix

Abstract: A n investigation of the effect of addition of Bi impurities on the electrical, optical and thermoelectric properties of vacuum evaporated amorphous thin films of Ge,,Te,,_,Bi, (x = 0, 0.19, 2.93 and 7.35) has been carried out. The synthesized thin films were characterized by x-ray diffraction and electron probe microanalysis. Analysis of the results revealed that Bi modification of the amorphous semiconducting thin films does not induce a clear-cut carrier sign reversal. This is in contrast to the observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…With the further increase in the content of dopant atoms, the trend of decrease continues. The same effect has also been observed with the other chalcogenide glasses with bismuth as dopant [7][8][9].…”
Section: Methodssupporting
confidence: 80%
“…With the further increase in the content of dopant atoms, the trend of decrease continues. The same effect has also been observed with the other chalcogenide glasses with bismuth as dopant [7][8][9].…”
Section: Methodssupporting
confidence: 80%
“…10. A qualitative explanation for the absence of a p-n transition in these films has been proposed by us (Bhatia et al 1995). In several other studies (Solin andPapatheodoru 1977, Nemanich, Cornell, Hayes andStreet 1978) on chalcogenides, it has been shown that thin films prepared by vacuum evaporation onto the substrates, held at temperatures below the glass-transition temperature, and of nominally the same composition as the coresponding bulk material, display very different types of bond distribution.…”
Section: Electronic Transportmentioning
confidence: 72%
“…However, the mechanism of the p-n transition still remains poorly understood. In a recent communication we have reported that thin films of Ge 20 Te s0 _ x Bi x do not exhibit a p-n transition up to x=7-35 like the one observed in bulk glasses at x = 3-5at.% (Bhatia, Singh, Kitagawa, Kishore and Suzuki 1995). Contrary to this behaviour, the two systems Ge-S-Bi and Ge-Se-Bi show a p-n transition in both thin-film forms (Bhatia et al 1988).…”
Section: §1 Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…This problem can be overcome by alloying Se with some impurity atoms (Bi, Te, Ge, Ga, Sb, As, etc), which gives higher sensitivity, higher crystallization temperature and smaller ageing effects. Several workers have studied the effect of bismuth on the optical and electrical properties of chalcogenide materials [9][10][11]. However, not much work has been reported on the effect of bismuth on the photoconductivity of the Se-Te matrix.…”
Section: Introductionmentioning
confidence: 99%